The handbook for enhancing professional practice : using the framework for teaching in your school - Danielson, Charlotte (Alexandria, VA : Association for Supervision and Curriculum Development, 2008)
International education consultant Charlotte Danielson provides guidance and tools for improving the professional practices of teacher educators, teachers, administrators, and others, covering teacher preparation, recruitment, hiring, evaluation, and mentoring; peer coaching; self-directed professional inquiry; and professional development.
Introduction -- Evidence of teaching -- Promoting professional learning -- Using the framework across the career spectrum -- Using the framework for teaching for teacher evaluation -- Using the framework for teaching for self-directed professional inquiry -- Recommended procedures for teacher evaluation -- Appendix A : instruments to support teacher evaluation and professional learning -- Appendix B : artifacts of teaching.
Includes index.
Professional
Keywords: Educational planning -- Handbooks, manuals, etc; Professional education -- Handbooks, manuals, etc; Teaching -- Handbooks, manuals, etc; Educational planning -- Handbooks, manuals, etc; Professional education -- Handbooks, manuals, etc; Teaching -- Handbooks, manuals, etc